The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4028/www.scientific.net/msf.740-742.217
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleation and Propagation of Threading Dislocations with C-Component of Burgers Vector in PVT-Grown 4H-SiC

Abstract: Studies of threading dislocations with Burgers vector of c+a have been carried out using synchrotron white beam X-ray topography. The nucleation and propagation of pairs of opposite sign threading c+a dislocations is observed. Overgrowth of inclusions by growth steps leads to lattice closure failure and the stresses associated with this can be relaxed by the nucleation of opposite sign pairs of dislocations with Burgers vector c+a. Once these dislocations are nucleated they propagate along the c-axis growth di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…While the mutual interaction of threading c+a and -c+a dislocations during cooling also forms 2a dislocation, this phenomenon was observed in bulk 4H-SiC by cross-sectional X-ray topography. 30,31 In this case, 2a dislocations are limited to the segment where the c+a and -c+a dislocations interact and both sides of the 2a dislocation are constructed from c+a and -c+a dislocations. Recently, we found that a complex dislocation both sides of an a 1 dislocation segment consist of a 2 and a 3 dislocations (a 1 =a 2 +a 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the mutual interaction of threading c+a and -c+a dislocations during cooling also forms 2a dislocation, this phenomenon was observed in bulk 4H-SiC by cross-sectional X-ray topography. 30,31 In this case, 2a dislocations are limited to the segment where the c+a and -c+a dislocations interact and both sides of the 2a dislocation are constructed from c+a and -c+a dislocations. Recently, we found that a complex dislocation both sides of an a 1 dislocation segment consist of a 2 and a 3 dislocations (a 1 =a 2 +a 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…101) Recent studies using synchrotron X-ray topography revealed that the majority of TSDs possess a Burgers vector of 1c + a. 102,103) This means that these TSDs are not pure screw dislocations, but mixed dislocations.…”
Section: Dislocations In Sic Boule Crystalsmentioning
confidence: 99%
“…TSDs usually propagate almost along the <0001> direction. Recent studies using synchrotron x-ray topography revealed that many of TSDs possess a Burgers vector of c + a [55,56], which means that a significant portion of TSDs is not of pure screw type but mixed dislocations. TSDs are basically replicated from a seed crystal.…”
Section: Dislocationmentioning
confidence: 99%